The South African Headquarter Company Regime: can this be considered an effective intermediary holding company regime? - Porter, Nicole (My University, 2014)
Africa is considered to be an emerging market, due to the large number of industries investing into Africa as a result of its low cost of employment and the volume of natural resources. Recently SARS has recognized the benefits of South Africa as an ideal location in which to establish an intermediary holding company through which investments into Africa may be channelled. There are a many factors that contribute to this, such as the wide treaty network established by South Africa, the growing economic sector and the close proximity to other African countries. In order to be considered an effective regime, the newly introduced Headquarter company regime (the new South African HQCR) will have to illustrate that the best practice characteristics required in an intermediary holding company jurisdiction are in fact present in South Africa. Even if these characteristics are present, the there are still a number of other factors that may hinder the effectiveness of such a regime. The most noticeable of which is the attractiveness of other well known and established headquarter company regimes such as Mauritius. Mauritius offers an attractive intermediary holding company regime to offshore investors due to the close proximity to Africa, the lack of exchange control regulations, large treaty networks with well-negotiated rates and the low effective tax rate. Should South Africa be able to compete with these traits, this may pose a risk that South Africa will be considered to participate in harmful tax practices. In these instances, the shifting of profits to a lower tax jurisdiction would likely result in double taxation through the non-applicability of DTAs. This view coincides with the substantial move against abuse of DTAs in what is referred to as the one world tax system. The purpose of this paper is therefore to consider whether or not the new South African HQCR established in South Africa will be considered as an effective regime based on the characteristics provided and whether or not this regime will be able to compete with other more prominent regimes such as Mauritius. Further considerations are also addressed as to whether or not the regime may be viewed as a harmful tax regime. The success of the regime is imperative on this consideration as strong initiatives are being undertaken worldwide to avoid the erosion of a countries tax base. In light of this it has become an increasingly difficult to promote a Headquarter company regime that is in conflict to these initiatives. The purpose of this paper is to establish whether or not SARS has managed to establish an effective headquarter company in light of all of the above.